Domestic biowaste drying as a pretreatment method to produce a stabilised biological resource. (3rd October 2019) - Sotiropoulos, A.; Xydis, George; Yard, Mishel; Vakalis, Stergios
The results of the use of the domestic biowaste drying method for the effective dehydration of the OFHMSW and the production of lignocellulosic biomass from this waste fraction are presented within this article. It presents the methodology and results produced from the first laboratory operation of a prototype household waste dehydration unit for the drying of household biowaste at source through the effective removal of its water content by using the heated air-drying process. The use of domestic dehydration technique revealed the substantial mass reduction that reached a maximum of 78%w/w, while the final product's carbohydrate content and suggests its further use to produce biobased chemicals and bioenergy. 39.99%w/w of the target material, more than 40%w/w of the material may be converted into sugars through fermentation and from there to ethanol. Moreover, 36.11 of the already existing sugars have the potential to be directly fermented to ethanol. Finally, considering a cost of 0.071 euro/kWh which is the mean value cost per kWh for the Greek household and energy consumption of 1, 001-1, 200 kWh which is also the average consumption of the Greek household, the maximum monthly cost for a family and a 24h operation was calculated to be 7.2 euros.